Implementasi Lesson Study Melalui Model Pembelajaran Problem Based Learning Materi SPLTV Kelas X IIK - Erlina Erlina; Eko Andy Purnomo (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
Developing and implementing Problem Based Learning using Lesson Study is very suitable for use in mathematics learning especially SPLTV. Moreover, this problem is related to daily life. Therefore this study aims to describe the implementation of lesson study with PBL learning models on the learning outcomes of the SPLTV substitution method in daily life in class X IIK 2. The researcher hopes that this research can improve student learning outcomes. This type of research is descriptive qualitative through Lesson Study activities consisting of three stages, namely Plan, Do and See with PBL models. Data collection techniques used were tests, observations and videos of the learning process in progress. The subjects in the study were class X IIK 2 as many as 35 students. So that student learning outcomes overall obtained from all groups was 96.43. This value is quite good, because above the KKM is 70 and close to perfect that is 100. Therefore, it can be concluded that the implementation of lesson study with PBL learning models on student learning outcomes of SPLTV material substitution method in class X IIK 2 went well and effectively.